A comparative study between semi-empirical oscillator strength parametrization and relativistic Hartree–Fock methods for computing the radiative parameters in Zr II spectrum. (October 2015) - Quinet, P.; Bouazza, S.; Palmeri, P.
Abstract: In the present work, we compare the radiative transition rates computed by two different semi-empirical approaches, based on a parametrization of the oscillator strengths and on a pseudo-relativistic Hartree–Fock model including core-polarization effects, for spectral lines in singly ionized zirconium. A detailed comparison with available experimental results is also reported and an overall good agreement is observed between all sets of data allowing us to provide new reliable oscillator strengths for a large amount of Zr II lines in the wavelength region from 1616 to 14746 Å. Moreover, we give radial integral values of the main atomic transitions deduced in this study: 〈4d 2 5p|r 1 |4d 2 5s〉=−3.1522 (0.0161), 〈4d 2 5p|r 1 |4d 3 〉=1.7605 (0.0107), 〈4d 2 5p|r 1 |4d 2 6s〉=−1.481 (0.794) and〈4d 2 5p|r 1 |4d 2 5d〉=2.289 (0.014). Highlights: Zr II fine structure analysis was newly achieved. Two semi-empirical approaches tested successfully recurring to comparison with experimental log gf data. Radial integral values of the main atomic transitions are given for the first time. Oscillator strength values are derived semi-empirically in a wide wavelength range: 1616–14, 746 Å.